Use of modern graphics programs in developing design thinking of engineers-builders - Mardov, Sanjar (Рroblems of engineering and professional education, 2024)
Today, the construction industry is developing rapidly. This, in turn, is aimed at forming the design thinking of engineers-builders, their graphic culture, as well as the creative potential of a person. There are many effective works on this front, especially in the teaching of construction drawing, educational efficiency is achieved using modern graphic software. The use of graphic programs designed for the field of architecture is an important tool in the development of future engineers-builders to become a more perfect staff in covering the topics of architectural construction drawing. Therefore, the importance of the application of graphic programs and their descriptions have a special place in elucidating the essence of design thinking.